(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the knowledge and compliance status regarding the ventilator associated pneumonia (VAP) prevention care bundle among nurses in the Intensive Care and Poison Control Department of a hospital in Hanoi in 2024. Subjects and Methods: A cross-sectional study was conducted on 13 nurses currently working in the Intensive Care and Poison Control Department who directly care for mechanically ventilated patients, with 157 instances of nurse-implemented VAP prevention care bundles recorded. Results: 61,5% of the nurses had adequate knowledge of VAP, with 92,3% understanding the benefits of head-of-bed elevation, and 100% knowing the appropriate timing for suctioning patient secretions. The rate of full compliance with the complete VAP bundle was 14%, while high-level compliance across the bundle was 31,2%. Specifically, compliance with hand hygiene reached 92,4%, oral care compliance was only 18,5%, and monitoring and suctioning of secretions reached 93%. Conclusion and Recommendations: The findings revealed that 61.5% of nurses demonstrated adequate knowledge regarding VAP prevention, while 38.5% did not meet the expected knowledge standards. Notably, the rate of full adherence to all preventive measures remained critically low at only 1.3%. These results highlight the urgent need for hospitals to strengthen ongoing professional education to enhance nurses’ knowledge and clinical practice, while also reinforcing workforce capacity and promoting interdisciplinary collaboration to reduce workload and ensure the effectiveness and safety of VAP prevention among mechanically ventilated patients.